Creative Destruction and the HIDCL - Butler, Christopher (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Not Available.DOI: http://dx.doi.org/10.3126/hn.v14i0.11248HYDRO Nepal JournalJournal of Water Energy and EnvironmentVolume: 14, 2014, JanuaryPage: 21-22